ANALYSIS OF THE POWER MARKET PRICING DYNAMICS REQUIRED FOR THERMAL GENERATION RENOVATION - A. Solyanik (Вестник университета, 2017)
The article deals with the methodical approach for the analysis of quantitative matching of long-run regulatory pricing policy with essential investment requirements of the electric power industry. The quantitative assessment of the power market prices necessary for financial viability of thermal generation renovation is given.